Control of interest rates - Barrantes Cáceres, Roxana (2022)
What justifies charging interest rates? What are its costs and/or benefits? Are certain people justified in being assigned comparatively higher interest rates? What is the effect of state control of interest rates? What does it mean to apply significantly high limits?This round table responds to each of these questions and many more, setting up a controversial debate around this area of financial law.